Management of Large Ovarian Tumors in Elderly Patients Using the Aron Alpha Method and Principles of Enhanced Recovery after Surgery - Kaoru Kakinuma; Toshiyuki Kakinuma; Ayaka Kaneko; Nobuhiro Takeshima; Kaoru Yanagida; Michitaka Ohwada (Gynecology and Minimally Invasive Therapy)
Objectives: We performed preoperative evaluations of giant ovarian tumors in older adult patients using the comprehensive geriatric assessment (CGA) and estimation of physiologic ability and surgical stress (E-PASS) scoring systems. We report a case in which the Aron Alpha method was performed, and perioperative management was performed using enhanced recovery after surgery (ERAS). Materials and Methods: We performed preoperative evaluations using the E-PASS scoring system and CGA on older adult patients with giant ovarian tumors, followed by the minimally invasive Aron Alpha method and perioperative management using ERAS. Results: The mean patient age was 75.8 ± 8.8 years; comorbidities included hypertension in three patients, hyperlipidemia in two, angina pectoris in one, cholecystitis in one, and lower extremity varicose veins in one. The mean tumor size was 21.0 ± 5.4 cm. The E-PASS scoring system showed a preoperative risk score of 0.7 ± 0.4, a surgical stress score of 0, and a comprehensive risk score of 0.3 ± 0.3. CGA showed that two patients had problems with activities of daily living and cognitive function. The mean duration of surgery was 89.0 ± 16.6 min, and the mean blood loss was 56.0 ± 65.4 mL. No surgery-associated complications were observed. No patients had prolonged hospitalization or a decline in activities of daily living. Conclusion: We showed the usefulness of performing detailed preoperative evaluations using CGA and the E-PASS system, followed by the minimally invasive Aron Alpha surgical method and perioperative management using ERAS in improving surgical outcomes in older adult patients with giant ovarian tumors.